A Systematic Literature Review (SLR) on the Influence of Integrated Marketing Communication Message Consistency on Consumer Trust in Green Products within the Context of Greenwashing Skepticism - Fiki Hayatuki; Rima Shobrina; Sertiningsih; Ni Putu Ayu Chandra Utari (Postgraduate University of Mataram, 2026)
The increasing occurrence of greenwashing has led to growing consumer doubts regarding sustainability claims and has weakened trust in green products. In this context, alignment within Integrated Marketing Communication (IMC) is an important factor in building and maintaining consumer trust. This study aims to examine in detail the effect of IMC message alignment on consumer trust in green products, particularly in the presence of consumer skepticism arising from greenwashing practices. This study employs a Systematic Literature Review (SLR) based on PRISMA guidelines by searching articles published between 2019 and 2025 in the Scopus, ScienceDirect, and Google Scholar databases. From a total of 90 articles identified, 12 articles were selected for in-depth analysis. The findings indicate that consistent IMC messages across various communication channels, supported by transparency and verifiable evidence such as third-party certifications, can reduce perceptions of greenwashing and enhance consumer trust. In contrast, inconsistent communication that is not aligned with genuine sustainability principles tends to increase consumer skepticism and reduce trust in brands. Overall, the results suggest that consistency in IMC is not merely a technical element of marketing communication but also an ethical approach that plays a crucial role in maintaining the credibility of green products amid increasing consumer skepticism.